The Problem of Training Future Engineer Personnel on the Basis of Cloud Technology in Technical Specialties of Higher Education - Ergashev Nuriddin G’ayratovich (Genius Publishing Group, 2022)
This article provides a theoretical analysis of the current state of the problem of preparing engineers for professional activities in the context of cloud technologies. In addition, the features of multi-stage preparation of teaching staff for professional activities using cloud technologies in the conditions of digital education and problems in their implementation are presente
Keywords: Digital education; cloud technologies; professional activities; level training